2016
DOI: 10.1111/mmi.13417
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and proteome analyses and the role of atypical calpain protein and autophagy in the spliced leader silencing pathway in Trypanosoma brucei

Abstract: Under persistent ER stress, Trypanosoma brucei parasites induce the spliced leader silencing (SLS) pathway. In SLS, transcription of the SL RNA gene, the SL donor to all mRNAs, is extinguished, arresting trans-splicing and leading to programmed cell death (PCD). In this study, we investigated the transcriptome following silencing of SEC63, a factor essential for protein translocation across the ER membrane, and whose silencing induces SLS. The proteome of SEC63-silenced cells was analyzed with an emphasis on S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…Inspecting TEM sections of SEC63 silenced cells, which induce the spliced leader silencing (SLS) pathway [53], revealed the presence of another type of vesicle, double-membrane autophagosomes [54], but not MVBs filled with ILVs, as in SmD1 silenced cells (S6 Fig); thus MVBs seem to be specific to cells secreting massive amounts of exosomes. Small numbers of exosomes are secreted from SEC63 silenced cells (S7 Fig).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspecting TEM sections of SEC63 silenced cells, which induce the spliced leader silencing (SLS) pathway [53], revealed the presence of another type of vesicle, double-membrane autophagosomes [54], but not MVBs filled with ILVs, as in SmD1 silenced cells (S6 Fig); thus MVBs seem to be specific to cells secreting massive amounts of exosomes. Small numbers of exosomes are secreted from SEC63 silenced cells (S7 Fig).…”
Section: Resultsmentioning
confidence: 99%
“…Note, that the proteome of SEC63 silenced cells shares changes which are common to SmD1 silenced cells, possibly because these two type of cells are inhibited in trans -splicing. However, changes that are specific to each of these perturbations were also identified [54]. The repelling activity of these two silenced cells clearly indicate that the repelling signal(s) is not specific to dying cells (Fig 11).…”
Section: Discussionmentioning
confidence: 99%
“…The proteome analysis of cells in which SLS had been induced by silencing of sec63 indicated an increase in the level of TIMRHOM1 protein (27). To verify this elevation, the level of the protein was examined upon SLS induced by sec63 silencing, and a fourfold increase was observed (Fig.…”
Section: Depletion Of Timrhom1 Affects Protein Translocation Across the Er Mitochondrial Function And Induces Slsmentioning
confidence: 91%
“…Cells expressing the SEC63 silencing construct and PK3 PTP-tagged protein (27), uninduced or induced for 2.5 days, were grown to a density of 2×10 7 cells ml -1`. The purification protocol used was essentially as described previously (33) from 10 10 cells but included the addition of phosphatase inhibitors to the extract (10 mM NaF, 1 mM sodium orthovanadate and 50 mM beta-glycerophosphate).…”
Section: Pk3 Purification and Mass-spectrometry Analysismentioning
confidence: 99%
“…Later, SKCRPs 7.1 and 7.2 were identified in T. brucei under persistent endoplasmic reticulum stress. The investigators concluded the essential role played by SKCRPs to induce PCD in under-stressed parasites [208] .…”
Section: Calpains (Calps)mentioning
confidence: 97%